2008
DOI: 10.1159/000153422
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Programming of Neuroimmunomodulation – Role of Adipocytokines and Neuropeptides

Abstract: Programming is an epigenetic phenomenon by which nutrition, environment and stress acting in a critical period earlier in life change the organism‘s development. This process was evolutionarily selected as an adaptive tool for the survival of organisms living in nutritionally deficient areas and submitted to stressful conditions. Thus, perinatal malnutrition turns on different genes that provide the organism with a thrifty phenotype. In conditions of abundant supply of nutrients, those programmed organisms can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
70
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(72 citation statements)
references
References 252 publications
2
70
0
Order By: Relevance
“…This association between early events (such as maternal smoking) and late consequences (such as obesity) exemplifies a phenomenon known as metabolic programming (de Moura et al 2008. Recently, some studies have shown that tobacco exposure in utero is associated with changes in gene methylation profile (Suter et al 2010(Suter et al , 2011, and the same event was observed in nicotine exposure (the main cigarette component)-changes the gene methylation pattern in fetal life are associated with long-term decreases in cortisol (Wang et al 2011).…”
Section: Introductionmentioning
confidence: 95%
“…This association between early events (such as maternal smoking) and late consequences (such as obesity) exemplifies a phenomenon known as metabolic programming (de Moura et al 2008. Recently, some studies have shown that tobacco exposure in utero is associated with changes in gene methylation profile (Suter et al 2010(Suter et al , 2011, and the same event was observed in nicotine exposure (the main cigarette component)-changes the gene methylation pattern in fetal life are associated with long-term decreases in cortisol (Wang et al 2011).…”
Section: Introductionmentioning
confidence: 95%
“…Researchers have only begun to define normal milk variation across populations and how it influences the postnatal period and beyond (Neville et al, 2012). Many of the emerging questions in human biology are linked to lactation, from unique aspects of primate Milligan and Bazinet, 2008) and human life histories (Fujita et al, 2011), parental investment (Fujita et al, 2012;Hinde, 2009;Powe et al, 2010), and developmental programming (de Moura et al, 2008;Hinde and Capitano, 2010;Miralles et al, 2006;Newburg et al, 2010;Palou et al, 2009;Pico et al, 2007;Prentice, 2005;Quinn, 2011;Quinn et al, 2012;Savino et al, 2009;Stocker and Cawthorne, 2008;Weyerman et al, 2007). In addition, lactation is implicated in human evolutionary biology, including the evolution of large brains and body fat (Kuzawa, 1998;Martin, 1981), childhood (Bogin, 1999;Konner, 2010;Sellen, 2007), reproductive timing (Al-Sahab et al, 2011) and the developmental origins of adult metabolism (Kuzawa and Quinn, 2009;Wells, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…This association has been named programing, which is defined as the phenomenon that putatively underlies relationships among nutritional experiences of early life and adult diseases (Lucas 1994, Barker 2003, Moura & Passos 2005, de Moura et al 2008.…”
Section: Introductionmentioning
confidence: 99%